Server Side Development with Node. js and Koa. js Quick Start Guide : Build Robust and Scalable Web Applications with Modern JavaScript Techniques. - Omole, Olayinka (Packt Publishing Ltd, 2018)
Every developer wants to build modular and scalable web applications. Modern versions of the JavaScript language have made this possible in Node.js, and Koa is a Node.js framework that makes it easy. This book is the ideal introduction for JavaScript developers who want to create scalable serverside applications using Node.js and Koa.js.